The Use of Cassy Lab in Calorimeter Experiment with Different Material as Learning Media - AJ Suharli; Isnania Isnania (Pendidikan Fisika Universitas Nurul Huda, 2026)
This study examined the effectiveness of Cassy Lab–based practicum activities in improving students’ understanding of temperature and heat concepts. A quantitative quasi-experimental method with a non-equivalent control group design was applied to 30 second-semester Physics Education students at Jambi University. Data were collected using pre-test and post-test instruments adapted from the Thermal and Transport Concept Inventory (TTCI). Analysis using IBM SPSS Statistics 26 included normality, N-gain, and independent t-test. Results showed that both groups improved, but the Cassy Lab group achieved a higher N-gain. The T-test indicated a significant difference between groups. These findings suggest that Cassy Lab–based practicum is effective in enhancing conceptual understanding and serves as an innovative technology-based learning medium. Further research should explore its impact on scientific process skills, critical thinking, and motivation with broader samples